A guidance framework for facilitating effective engineering student teams and its impact on individual learning. (1st January 2014) - Neill, Colin J.; DeFranco, Joanna F.
The ability of engineering students to work effectively in teams is a growing need expressed by both industry and academia. Consequently, an engineering student can expect to work on a number of teams during their studies and to have the outcomes of those efforts contribute meaningfully to their individual assessment. It is imperative, then, that those students are provided the guidance necessary to hone the skills of effective collaboration. We have developed a framework of guidance, the cognitive collaborative model, and report on it in this paper. Further, we demonstrate its efficacy in facilitating team mental model convergence and the concomitant improvement in team outcomes. Lastly, and critically, we have investigated whether those improved team experiences and outcomes lead to improvement in individual learning in accordance with the expectations from collaborative and social constructivist learning theories. Counter-intuitively, we find that this is not the case, and we report those results and suggest theoretical foundations for these findings.